Evaluating the Effectiveness of Marketing Communication Strategy in Economic Services Companies Empirical Study on a Sample of Mobile Phone Customers in Algeria - بوجنانة, فؤاد (Milev Journal of Research and Studies, 2019)
The aim of this study was to evaluate the effectiveness of marketing communication strategy in the economic service companies, By measuring the effectiveness of each element of the traditional and modern marketing communication mix, To achieve the objectives of the study, a questionnaire was distributed to the mobile phone customers in Algeria. Statistical Package for Social Sciences SPSS22 was used to analyze the questionnaire data, The study found that there is a high contribution to sales promotion in the effectiveness of the marketing communication strategy, while recording the average role of the other communication elements in the effectiveness of marketing communication strategy in the companies studied.